The Confluence of Biological, Rational and Unconscious Substrates: The Witness Metaphor in the Etiology of Power - Necșulescu, Alina (Acta Universitatis Danubius. Communicatio, 2024)
To comprehend the intricate power relations that shape intrapsychic and interindividual levels, a multifaceted approach is imperative, as these relations have been extensively contemplated and researched, yet they cannot be confined within a single theoretical framework. Consequently, no single field of enquiry possesses the capacity to comprehensively articulate a phenomenon and its attendant implications. With all these insights from these broad domains in mind, this article proposes the addition of a fourth scenario to Ivan Chase’s categorisation, which can also become an intrapsychic metaphor as an attitude towards self and a crucial function in shaping identity. The primary objective of this article is not to delineate a predetermined form of power, but rather to elucidate its developmental processes, its etiology, and the manifold external and internal factors that contribute to its manifestation. In this regard, it can be conceptualised as a narrative rather than a mere noun or verb.